Subjective experiences and perceptions of learning a second language through digital games: A case study of Chinese college students - Xiao, Xian; He, Gaoda (Frontiers in Psychology, 2023)
Recent years have seen a rapid proliferation of game-based learning applied in language class. Second language teaching and learning takes inspiration from the more and more matured game-based learning technology. Currently, educational games are regarded as a new technology with great potential. The game-based promotion of oral English has also become one of the research hotspots. This research carried out an empirical study on the subjective experiences and perceptions of using game-based second language learning, focus on the cultivation of the Chinese college students’ oral English. By using Unity 3D technology, “Digital Game-Virtual College” game software was developed for Chinese teenagers as the experimental carrier. 66 freshmen majoring in engineering in a university located in a first-tier city in southern China were invited as participants. Based on the courses of “College English—Reading and Writing” and “College English—Listening, Viewing and Speaking”, this research explored the game-based teaching of “Words Arena Contest” and “Words Talents” respectively. Analysis of the attitude and achievement data not only indicated the advantages and disadvantages of game-based learning. but also suggested the significant points in game-based learning software design. The results of tests and survey provide insight into the evaluation and reflection of the subjective experiences and perceptions of using digital game-based language learning. The results of this research not only can provide guidance for explore the psychological contributors and barriers on game-based second language learning, but also can shed some lights and give reference for the design of game-based second language learning software.